2010
DOI: 10.1016/j.ajic.2009.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of health information through social networks: Twitter and antibiotics

Abstract: Background This study reviewed Twitter status updates mentioning “antibiotic(s)” to determine overarching categories and explore evidence of misunderstanding or misuse of antibiotics. Methods One thousand Twitter status updates mentioning antibiotic(s) were randomly selected for content analysis and categorization. To explore cases of potential misunderstanding or misuse, these status updates were mined for co-occurrence of the following terms: “cold + antibiotic(s),” “extra antibiotic(s),” “flu + antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
410
0
17

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 632 publications
(431 citation statements)
references
References 15 publications
4
410
0
17
Order By: Relevance
“…In Kenya, Zurovac et al (2011) found the use of text messages to be efficient in the prevention and treatment of malaria. The use of social media platforms such as Twitter has also been found to be effective in health information dissemination (Scanfeld, Scanfeld & Larson, 2010). This demonstrates the potential for effectiveness of m-health in health information dissemination.…”
Section: Reproductive Health Information Access Among Rural Women Inmentioning
confidence: 82%
“…In Kenya, Zurovac et al (2011) found the use of text messages to be efficient in the prevention and treatment of malaria. The use of social media platforms such as Twitter has also been found to be effective in health information dissemination (Scanfeld, Scanfeld & Larson, 2010). This demonstrates the potential for effectiveness of m-health in health information dissemination.…”
Section: Reproductive Health Information Access Among Rural Women Inmentioning
confidence: 82%
“…Studies indicate that such online patient forums can serve as a powerful vehicle for (a) knowledge creation and utilization [1,2], (b) disseminating information to the patient community [3], (c) creating new products and services in partnership with patients (i.e., value co-creation) [2], (d) providing empathic support to patients [4], and (e) enhancing the image of the sponsoring organization [5].…”
Section: Commentarymentioning
confidence: 99%
“…Misinformation on online forums, blogs, websites, and social networking sites is likely to be a serious threat to patient well-being as well as to the patient-clinician relationship, with much misinformation (e.g., linking vaccinations and autism) being spread through social media sites such as Facebook and Twitter [3,6]. Although in certain instances, such misinformation sharing could be intentional (e.g., due to paid promotion of specific products), in other instances, it could be unintentional, as patients might truly believe that they are sharing valid information that would be of benefit to others.…”
Section: Preventing and Managing The Spread Of Misinformation Throughmentioning
confidence: 99%
“…Several other studies indicate that Twitter can be very useful for such purposes of monitoring and obtaining information relating to people's health behaviour.. For example, in [35] Twitter was identified as a way to gather and exchange important real-time health data. Also, as is noted in [16], 'Twitter presents an interesting yet underexplored tool for health-promoting activities', and 'Twitter might be a promising platform for leveraging social support to motivate health behaviour change'.…”
Section: The Twitter Environmentmentioning
confidence: 99%